2006
DOI: 10.1242/jcs.02796
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of chondroitin 6-sulphotransferase-1 facilitates Schwann cell migration during axonal growth

Abstract: Cell migration is central to development and post-traumatic regeneration. The differential increase in 6-sulphated chondroitins during axonal growth in both crushed sciatic nerves and brain development suggests that chondroitin 6-sulphotransferase-1 (C6ST-1) is a key enzyme that mediates cell migration in the process. We have cloned the cDNA of the C6ST-1 gene (C6st1) (GenBank accession number AF178689) from crushed sciatic nerves of adult rats and produced ribonucleotide probes accordingly to track signs of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…[8][9][10] To solve this problem, SCs genetically modified to alter their adhesive properties have been investigated. [11][12][13] In vertebrates, the neural cell adhesion molecule (NCAM) is expressed on axonal and SC membranes, and its function is influenced by polysialylation, a critical mediator of neural cell migration. 12 Polysialic acid (PSA) is a linear homopolymer of α2,8-Nacetylneuraminic acid, which is synthesized on NCAM by polysialyltransferase (PST) and sialyltransferase X (STX).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] To solve this problem, SCs genetically modified to alter their adhesive properties have been investigated. [11][12][13] In vertebrates, the neural cell adhesion molecule (NCAM) is expressed on axonal and SC membranes, and its function is influenced by polysialylation, a critical mediator of neural cell migration. 12 Polysialic acid (PSA) is a linear homopolymer of α2,8-Nacetylneuraminic acid, which is synthesized on NCAM by polysialyltransferase (PST) and sialyltransferase X (STX).…”
Section: Introductionmentioning
confidence: 99%
“…One study into injury-related CSST upregulation in the damaged cortex in rats found C6ST -1 (Accession: NM_016803.3) to be upregulated while another study showed increased 6 and 4,6-sulphated GAGs, and a third study of injured spinal cord found an increase in 4-sulphated GAG [21][22], [26]. C6ST -1 upregulation has been associated with Schwann cell-assisted guidance of axons through the developing and injured environment [27].…”
Section: Introductionmentioning
confidence: 99%
“…Of the molecular factors responsible for Schwann cell migration, NGF and its Schwann cell receptor (low-affinity NGF receptor or LNGFR) and 4C5 Schwann cell surface antigen were reported to mediate Schwann cell migration on denervated sciatic nerve (Anton et al, 1994a;Yfanti et al, 2004). Oxidized galectin-1, which is produced from Schwann cells and neurons and functions as a cytokine, and extracellular matrix components, such as laminin (merosin) and products of chondroitin 6-sulphotransferase activity, were reported to promote axonal regeneration by Schwann cell migration (Fukaya et al, 2003;Anton et al, 1994b;Liu et al, 2006). These studies implicate the importance of the molecular interaction of Schwann cells with the environment, but the events within the migrating Schwann cell in response to injury are largely unknown.…”
Section: Introductionmentioning
confidence: 99%